Dendrimers as novel class of polymeric corrosion inhibitors: A review - Verma C.; Ebenso E.E.; Quraishi M.A. (My University, 2025)
Dendrimers are a new class of highly branched, nano-sized, monodisperse macromolecules that have several fascinating physical and chemical characteristics. They are highly soluble in the polar solvents, contain several surface functionality and high surface area which makes them suitable reagents for industrial and biological applications. Recently, several dendrimers have been investigated as effective corrosion and scale inhibitors for metallic and silica corrosion using experimental and theoretical methods. Generally, dendrimers become effective by forming insoluble metal-dendrimer or silica-dendrimer composite on the surface. Their inhibition performance of dendrimers have been measured using several experimental such as weight loss, electrochemical (EIS and PDP) and surface (EDX, SEM and AFM) as well as computation techniques such as molecular dynamics simulation and DFT based quantum chemical calculations. The interactions between metal surface and dendrimers can be explain through some common parameters such as E HOMO , E LUMO , ∆E, electronegativity (χ), hardness (η), softness (σ), dipole moment (µ) and fraction of electron transfer (∆N). Present book chapter deals with detail description on the corrosion inhibition and anti-scaling behaviours of dendrimers for metals and silica in several electrolytic media. © 2018, Russian Association of Corrosion Engineers. All rights reserved.